The Therapeutic Potential of Anthocyanins: Current Approaches Based on Their Molecular Mechanism of Action - Salehi, Bahare; Sharifi-Rad, Javad; Cappellini, Francesca; Reiner, Željko; Zorzan, Debora; Imran, Muhammad; Sener, Bilge; Kilic, Mehtap; El-Shazly, Mohamed; Fahmy, Nouran M.; Al-Sayed, Eman; Martorell, Miquel; et al. (Frontiers in Pharmacology, 2020)
Anthocyanins are natural phenolic pigments with biological activity. They are well-known to have potent antioxidant and anti-inflammatory activity, which explains the various biological effects reported for these substances suggesting their antidiabetic and anticancer activities, and their role in cardiovascular and neuroprotective prevention. This review aims to comprehensively analyze different studies performed on this class of compounds, their bioavailability and their therapeutic potential. An in-depth look in preclinical, in vitro and in vivo, and clinical studies indicates the preventive effects of anthocyanins on cardioprotection, neuroprotection, anti-obesity as well as their antidiabetes and anticancer effects.